The role of spiritual factors in people living with chronic pain: a qualitative investigation. Issue 2 (3rd July 2017) - Corbett, Mandy; Lovell, Melanie; Siddall, Philip J.
ABSTRACT: The role of existential and spiritual factors has been relatively under-explored in the field of chronic pain. The aim of this study was to explore in detail how people understood the spiritual dimension and, in particular, its relevance for and impact on their experience of pain. We undertook a qualitative study using semi-structured interviews and Interpretative Phenomenological Analysis with six people with chronic pain. Participants' views of the spiritual dimension varied widely with some seeing it within a religious context and others describing a strong sense of the spiritual that had no religious context. Meaning and purpose were, however, consistent elements of all participants' spirituality. Pain had an impact on people's sense of meaning, purpose and identity which was very much intertwined with their relationships with others and, for some, a transcendent connection to nature or a higher being. The ability to redefine or recapture a sense of meaning, purpose, and identity through these relationships was central to their ability to adjust successfully to the presence of chronic pain.